Penetrasi Sosial Hubungan Pacaran Pada Perempuan Yang Hamil Di Luar Pernikahan (Studi Deskriptif Kualitatif pada Perempuan di Desa Bandar Setia) - Siti Aisyah Nenggelis; Rehia K. I. Barus; Bahrum Jamil (Universitas Medan Area, 2019)
The purpose of this research was to find out and understand how the penetration stages are applied on their dating relationship. There are four of social penetration stages. First, is introduction stage. Second, is open up stage. Third, ares commitment and comfort stage. Fourth, are formality, honesty, and intimacy stage. This research’s type is qualitative descriptive is data from interview, observation and documentation that have been done, then clearly described. The informant selection technique used in this research was “snowball technique”. The snowball technique are often used to find and recruit hidden informants, namely individuals who aren’t easily accessible to researchers through other informant selection techniques. The conclusion of this research was the three informants applied the all social penetration stages on their dating relationship with their babies’ father however, each stage should have a long time to process, it is applied too quickly by the three informants. Initially, the three informants only wanted to undergo dating relationship as in general without any sexual elements. But, one, two, three informants were forced to have intercourse with their babies’ father. The consequence, the three informants were very sorry for having premarital sex.